T‐cell replete haploidentical stem cell transplantation attenuates the prognostic impact of FLT3‐ITD in acute myeloid leukemia: A report from the Acute Leukemia Working Party of the European Society for Blood and Marrow Transplantation. Issue 6 (23rd March 2018) - Canaani, Jonathan; Labopin, Myriam; Huang, Xiao‐Jun; Arcese, William; Ciceri, Fabio; Blaise, Didier; Irrera, Giuseppe; Corral, Lucia Lopez; Bruno, Benedetto; Santarone, Stella; Van Lint, Maria Teresa; Vitek, Antonin; et al.
Abstract: Acute myeloid leukemia (AML) patients harboring the FLT3‐ITD mutation are considered a high risk patient subset preferentially allocated for allogeneic stem cell transplantation in first remission. Whether FLT3‐ITD retains a prognostic role in haploidentical stem cell transplantation (haplo‐SCT) is unknown. To analyze the prognostic impact of FLT3‐ITD in haplo‐SCT, we performed a retrospective analysis of the multicenter registry of the acute leukemia working party of the European Society for Blood and Marrow Transplantation. We included all adult AML patients with known FLT3 status who underwent a first T‐cell replete related haplo‐HCT in first complete remission from 2005 to 2016. We evaluated 293 patients of whom 202 were FLT3 wt and 91 were FLT3‐ITD mutated. FLT3‐ITD patients were more likely to be NPM1 mutated as well as be in the intermediate risk cytogenetic risk category. In multivariate analysis, patients with FLT3‐ITD had comparable rates of relapse incidence [Hazard ratio (HR) = 1.34, confidence interval (CI) 95%, 0.67‐2.7; P = .9] and leukemia‐free survival (HR = 0.99, CI 95%, 0.62‐1.57; P = .9) to those of FLT3 wt patients. Overall survival, the incidence of nonrelapse mortality, and graft versus host disease‐free/relapse‐free survival were not significantly impacted by FLT3‐ITD status. Furthermore, relapse and overall survival were comparable between FLT3‐ITD patients transplanted from various donor pools, namely matched siblings, unrelated donors, haplo‐SCT). Finally, subset analysis of patients with intermediate risk cytogenetics confirmed the absence of a prognostic impact of FLT3‐ITD also for this patient segment. In AML patients undergoing T‐cell replete haplo‐SCT, the FLT3‐ITD mutation possibly does not retain its prognostic significance.